Health practices and feminine body construction - Hillesheim, Betina; Universidad de Santa Cruz do Sul (Universidad Santo Tomás, Colombia, 2005)
This article discusses how health practices focused on women construct significance on health and feminine body since such practices produce certain ways of being, living and feeling that build ways of being woman or man. Data from a research that took place in an academic health service, with women that went under breast and uterus cancer prevention examinations from May to December 2002 are shown. Data production was accomplished through health practices observations and interviews with service's users. Feminist Studies and mainly authors with post-structuralists theorizations were the theoretical bases. We hope this work contributes to the reflection about health practices focused on women, making possible a broader understanding about feminine and allowing room to ways of being in the world other than those the hegemonic point of view states as appropriate. Key words: feminine body, health and genre.